RELATIONSHIP BETWEEN ADMINISTRATIVE SKILLS OF EDUCATIONAL INSTITUTION ADMINISTRATORS AND OPERATIONS ACCORDING TO THE EDUCATIONAL QUALITY ASSURANCE SYSTEM WITHIN EDUCATIO NAL INSTITUTIONSOF SCHOOLS UNDER THE SECONDARY EDUCATION SERVICE AREA OFFICE BANGKOK 2 - Kasa, Phornpavee; Rumakhom, Vassiga; Chaowarakul, Jitiyaporn (Journal of MCU Nakhondhat, 2025)
The objectives of this research were 1) To study administrative skills of educational institution administrators of schools under the Secondary Education Service Area Office Bangkok 2 2) To study operations according to the educational quality assurance system within educational institutions of schools under the Secondary Education Service Area Office Bangkok 2 and 3) To study relationship between administrative skills of educational institution administrators of schools under the Secondary Education Service Area Office Bangkok 2. This is a quantitative research study using simple random sampling to obtain a sample group of 378 teachers. A questionnaire was used as a data collection tool, and the data were analyzed using statistical methods including frequency, percentage, mean, standard deviation, and Pearson’s correlation coefficient. The results have shown as followed, 1) Administrative skills of educational institution administrators of schools under the Secondary Education Service Area Office Bangkok 2 were at a moderate level ( = 3.49). When considering individual aspects, the technical skills had the highest average ( = 4.01), while human skills had the lowest average ( = 2.53); 2) Operations according to the educational quality assurance system within educational institutions of schools under the Secondary Education Service Area Office Bangkok 2 was generally at a high level ( = 4.19). Among the individual aspects, the development of educational management plans aimed at quality according to educational standards had the highest average ( = 4.22), while the evaluation and inspection of the quality of education within schools had the lowest average ( = 4.13); and 3) There was a very strong positive correlation (r = 0.819) between the management skills of school administrators and the implementation of the internal quality assurance system in schools under the Bangkok Metropolitan Secondary Educational Service Area Office, District 2.